Experiences of epileptic adults with searching for and maintaining a job in the Czech republic: qualitative study - Chrastina, Jan; Vysloužilová, Marie (Social Welfare: Interdisciplinary Approach, 2018)
Epilepsy is the most frequent seizure disorder affecting both social and occupational life of the patients. On the open labour market, these individuals might encounter a number of obstacles, lack of understanding, and limitations. Although epileptic employees do not currently require any adjustments to their working environment in order to improve or perform their jobs, they are often confronted with prejudices, misguided attitudes, stigmatization, and lack of awareness on the part of the employees but also the patients themselves. The presence of epilepsy has multiple implications for occupational life in terms of limited job opportunities on the labour market and decreased chances of getting/maintaining a job. The objective of the present qualitative study was to identify, analyse and describe the experiences and needs of epileptic persons concerning their employment. The study was of an exploratory-descriptive nature and involved 25 epileptic adults (17 women and 8 men) with a minimum of 6 months of occupational experience in their current job. The data were obtained by means of the unfinished sentences method (total of 16 sentences) and were analysed using an interpretative content analysis. The content of the unfinished sentences reflected the following timeline: (1) Link to the disease (4 sentences) – (2) Experiences of epileptic persons with searching for a job (5 sentences) – (3) Experiences with performance of the job (7 sentences). The participants perceive epilepsy as a barrier to their occupational self-actualization, some of the participants consider themselves as persons with health disability. The social dimension included the participants’ experience with meeting people and their desire for a job, which is often inaccessible due to their disease. The participants consider the process of searching for a job a journey full of hardship and hard-earned experience. The factors that affect getting a job are as follows: stage of disease, employer’s requirements, but also personal efforts and luck. An important aspect is the very first personal presentation during a job interview. A decisive aspect is disclosing the diagnosis during a job interview, or concealing the health status in order to get the job. The participants appreciate when the employer allows adjustment to the working hours or home office, or accepts the participants’ health status. The participants agree that an important aspect is positive assessment by their colleagues; they appreciate their helpfulness, fair approach, support and motivation. They appreciate if their colleagues do not show sympathy. One of the problematic aspects related to employment includes fear of seizures, seizures at work, their frequency and intensity. These and other manifestations of the disease (for example unrest, inattention, fatigue and lack of concentration) raise uncertainty and fear of losing the job. According to the participants, a significant barrier is a low level of awareness and the resulting impoliteness of other people. Despite the fact that some of the participants report unpleasant feelings when talking about their disease and consider the disclosure of this information an unpleasant necessity due to possible help required later, being employed is an opportunity for them to work fully and independently, achieve success, become self-reliant, self-confident, responsible and important. These are all qualities that are associated with being employed.